Development of Digital Mathematics Teaching Materials Based on GeoGebra and Desmos to Measure Teachers’ Creativity through a Promote Action Approach - Farit Dwi Ratnasari; Wiwin Sri Hidayati; Jauhara Dian Nurul Iffah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to develop digital mathematics teaching materials to measure teacher creativity. The study used the ADDIE development model. Respondents were teachers and students of grade XII of SMA Diponegoro and SMA Rijan Mojokerto. The research instruments included teaching material validation sheets, creativity observation sheets, teacher and student response questionnaires, interview guidelines, pre-tests, and post-tests. The results showed that the digital mathematics teaching materials met the criteria of being valid, practical, and effective. Validity was established by two validators, who scored 74 and 78, respectively. Practicality was demonstrated by the results of the analysis of teacher response questionnaires from the two schools, with percentages of 97% and 100%, and student response questionnaires, which yielded percentages of 85% and 87%, both falling within the very practical category. Effectiveness results were obtained by comparing the differences and increases in post-test scores with those from pre-tests. The test results at SMA Rijan showed an average increase of 19.28, and at SMA Diponegoro, 19.57. Meanwhile, the results of measuring teacher creativity, based on the analysis of teacher creativity observation sheets, yielded a score of 4, indicating a very good category. The results of this study show that the teaching materials developed can be used to measure teacher creativity.